GED test for dummies - Shukyn, Murray; Shuttleworth, Dale E. (Dale Edwin) 1938-; Krull, Achim K. (For dummies., 2015)
Presents subject review, full-length practice tests with answer explanations, and test-taking strategies to help readers prepare for and score higher on the high school equivalency test.